Konsep Periwayatan Hadis Era Nabi Hingga Kodifikasi - T, Tawarati; Ningsih, Fitri; Amin, Muhammadiyah; Yahya, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The birth of hadith is directly related to the personality of the Prophet Muhammad SAW, as the source of hadith, where he had indeed guided his people for approximately 23 years, and that period was the period of revelation (the Qur'an), along with that the hadith also came out. The birth of hadith during the time of the Prophet was an interaction of the Prophet as Mubayyin (giver of an explanation) regarding the verses of the Qur'an to his friends or to other people, in order to convey the message, and also because of various life problems that were being faced by the people and were in great need of solutions or solutions from the Prophet SAW, then his friends understood and memorized what they had received from the Prophet SAW. The results of this study show that First, the reasons for the prohibition of writing hadith were not due to the ignorance of Muslims in writing activities at that time, in fact they had known writing since the beginning of Islam, even before Islam. Second, the dominant factor in the prohibition of writing hadith was the fear of mixing the Qur'an and asSunnah. In addition, so that the project of writing the Qur'an is not disturbed by the writing of the hadith. Third, there is no contradiction between the hadiths about the prohibition and the permission of writing hadith, because the hadiths about the prohibition appeared first and when the reasons for the prohibition disappeared, the hadith about the permission of writing appeared. Fourth, the activity of writing hadith in the time of the Prophet Muhammad had existed as evidenced by the existence of hadith records in some of the companions known as 'as-Sahifah', but this activity was only individual and on a small scale, while the activity of writing and collecting hadith on a large scale began during the time of the caliph Umar bin Abdul Aziz.